EKSPLORASI PENGETAHUAN CALON GURU MATEMATIKA TENTANG PROSES PENALARAN MATEMATIS SISWA - Rahma Febriyanti; Novitasari Novitasari; Nur Ilmayasinta; Dita Fitria Wati (IKIP Siliwangi, 2022)
The development of mathematical reasoning is part of an important process that needs to be taught to students, as reflected in teacher education. This study focuses on the education of prospective teachers of mathematics which aims to describe the knowledge of prospective teachers about students' mathematical reasoning processes. The subjects of this study were prospective mathematics teacher students who were selected by purposive sampling. The instruments used include math assignments and interview guidelines. Data analysis techniques with data reduction, data presentation, data interpretation, and making conclusions. The results of this study indicate that the knowledge of the reasoning process carried out by prospective mathematics teachers is organized into 3 levels of knowledge in each reasoning process that appears, namely generalizing, justifying, classifying, and exemplifying. At the level of knowledge of the reasoning process, student teacher candidates still have difficulty in analyzing students' reasoning processes, using the meaning of terms in everyday life, and only considering the correct reasoning process. An important aspect of the reasoning process is developing knowledge by completing the means as a medium to understand the reasoning process in each student's learning.